PELAYANAN SPIRITUAL PADA PASIEN, SIAPA PEDULI? - Sofia Gusnia (Jurnal Teologi (Journal of Theology), 2012)
Nurses often express a variety of reasons that make them less or even no attention to spiritual issues of patients but the nurses believe that human beings as bio-psycho-socio-cultural and spiritual creatures as a whole respond to the changes occuring. Nursing care provided by nurses can not be separated from the spiritual aspect as an integral part of the nurse's interaction with clients. Nurses through the nursing process should help patients to accept the pain and to find meaning and significance of their suffering. Only a relationship with God, making life and relationships among others become more meaningful in facing the failure, suffering and death. Spiritual care for patients becomes a reflection of the nurses if they are spiritually healthy or not. Nurses will not be able to carry on the spiritual needs of patients when he himself have a spiritual problem.